Development of antifouling ultrafiltration membranes by surface modification. (1st July 2010) - Shobana, K.H.; Ramya, R.; Mohan, D.
Poly(vinylidene fluoride) (PVDF) membranes were prepared by phase inversion technique. The effects of polystyrene (PS) concentrations on the blend membrane performance were investigated. The membranes were characterised in terms of shrinkage ratio, pure water flux, and porosity. The hydrophobicity of the membrane was modified by poly(vinyl alcohol) (PVA) through adsorption and crosslinking. The performance of the modified membrane was investigated for its antifouling property with BSA solution. 70/30wt% blend PVDF/PS blend membrane showed better antifouling property than other membranes owing to its high hydrophilic property incorporated by adsorption crosslinking of PVA on to the membrane.